Optimization of recombinant Analgesic peptides production in Bacterial Cultures by using Taguchi Method - Dr.J.Vekateshwara Rao (International Journal of Advanced Science and Technology, 2020)
E.coli has several advantages over other higher organisms like yeast, plant, insects and other mammalian cells in production of recombinant proteins and scale up of production process. E.coli has three chambers for production of recombinant proteins that incorporates a periplasm, cytoplasm & extracellular medium. Depending upon the chambers utilized for synthesis, various methods can be developed for optimum levels production of functional analgesic opioid peptides. The reduction of cytoplasm makes a desirable region for high leve production of analgesic opioid peptides, that do not demand disulfide bond making for their poteintialities. E. coli is one of the favourite host for the synthesis of various small peptides, however it is one of the toughest for production of full protein due to of be deficient in glycosylation process and weak assemblage of peptide molecules. The full length studies of protein in Eschrischia coli, although the productivity were not as desired ( 149 mg in 72-h cultivation soluble full length of IgG/L). However, in E. coli, up to 4g/l of high level volumetric productivities can be obtained using high cell density cultivations (HCDC)